Problems and prospects of development of the national legal ideology in the context of globalization - Калюжний, Ростислав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article is devoted to the legal nature of ideology as a political and legal phenomenon. The author substantiates theoretical and methodological foundations of the ideology, analyzes the views of Ukrainian scientists on the mechanism of its formation under conditions of globalization and transformation of the national legal system of Ukraine.